Quantification of in vivo gastric fluid volume in Bama miniature pigs in fasted state. (18th September 2018) - Guo, Hui; Wang, Cuncai; Liu, Zhen; Gu, Huayong; Li, Yuwen; Zhao, Li; Hou, Ranran; Zhu, Jiajia; Ho, Harvey; Hao, Zhihui
Abstract: Although the study of bioequivalence waivers in humans is already well‐established, their application and translation into animals, which are complicated by differences in physiology, have only recently become subjects of interest. The main purpose of this paper is to quantify the liquid volume affecting drug dissolution in pig stomachs. We used magnetic resonance imaging (MRI) to scan 18 Bama miniature pigs weighing 15, 30 or 50 kg. Amira 6.0.1 software was used for 3D image processing. We found that the gastric fluid volume had a linear relationship with the weight of pig (R 2  = 0.9935) over this weight range. The pig weight, therefore, could be used as a surrogate for the fasted gastric fluid volume. After combining data of gastric fluid secretion and drinking water volumes, our results could be used as a reference for the evaluation of oral drug absorption in pigs.